Regulatory modules controlling maize inflorescence architecture - Eveland, Andrea L.; Goldshmidt, Alexander; Pautler, Michael; Morohashi, Kengo; Liseron-Monfils, Christophe; Lewis, Michael W.; Kumari, Sunita; Hiraga, Susumu; Yang, Fang; Unger-Wallace, Erica; Olson, Andrew; Hake, Sarah; et al. (Genome Research, 2014)
Genetic control of branching is a primary determinant of yield, regulating seed number and harvesting ability, yet little is known about the molecular networks that shape grain-bearing inflorescences of cereal crops. Here, we used the maize (Zea mays) inflorescence to investigate gene networks that modulate determinacy, specifically the decision to allow branch growth. We characterized developmental transitions by associating spatiotemporal expression profiles with morphological changes resulting from genetic perturbations that disrupt steps in a pathway controlling branching. Developmental dynamics of genes targeted in vivo by the transcription factor RAMOSA1, a key regulator of determinacy, revealed potential mechanisms for repressing branches in distinct stem cell populations, including interactions with KNOTTED1, a master regulator of stem cell maintenance. Our results uncover discrete developmental modules that function in determining grass-specific morphology and provide a basis for targeted crop improvement and translation to other cereal crops with comparable inflorescence architectures.
10.1101/gr.166397.113